2008
DOI: 10.1021/bi801076c
|View full text |Cite
|
Sign up to set email alerts
|

Global Conformational Dynamics in Ras

Abstract: Ras and its homologues are central to regulation of a multitude of cellular processes. Ras in complex with GTP binds and activates its downstream signaling partners. (31)P NMR studies indicated that the Ras-GTP conformation is heterogeneous on a millisecond time scale, but details of its conformational dynamics remain unknown. Here we present evidence that the conformational exchange process in human H-Ras complexed with GTP mimic GppNHp is global, encompassing most of the GTPase catalytic domain. The correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 24 publications
6
80
0
Order By: Relevance
“…The ␣3-helix and P-loop were thought to be rather immobile from crystallographic studies. However, the backbone amide 15 N spin relaxation rcCPMG measurements by O'Connor et al (32) suggested that they exhibit a significant mobility upon state transition, which is further supported by our latest study 4 of 15 N relaxation times and heteronuclear nuclear Overhauser effects of H-RasT35S-GppNHp. As already proposed (21), the various events relevant to the state transition could be targeted for development of Ras inhibitors, i.e.…”
Section: Conservation Of the Roles Of The Novel Intramolecular Interasupporting
confidence: 73%
“…The ␣3-helix and P-loop were thought to be rather immobile from crystallographic studies. However, the backbone amide 15 N spin relaxation rcCPMG measurements by O'Connor et al (32) suggested that they exhibit a significant mobility upon state transition, which is further supported by our latest study 4 of 15 N relaxation times and heteronuclear nuclear Overhauser effects of H-RasT35S-GppNHp. As already proposed (21), the various events relevant to the state transition could be targeted for development of Ras inhibitors, i.e.…”
Section: Conservation Of the Roles Of The Novel Intramolecular Interasupporting
confidence: 73%
“…A coordinated analysis of X-ray and NMR data uncovered a correspondence between the regions of the protein that are sensitive to cooling and those that are mobile in solution. To test the generality of this idea, we analyzed the small GTPase H-Ras bound to the GTP-analog, GMPPNP, by comparing high-resolution room-temperature (1.31 Å) and cryogenic (1.26 Å) X-ray data (25) to NMR relaxation dispersion experiments (26).…”
Section: Resultsmentioning
confidence: 99%
“…A challenging aspect of directly targeting RAS in its GTPbound form is the fact that switch I and switch II are disordered in solution (11,58,61), as is also the case in RAS-GDP (62), making it difficult for small molecules to bind. When bound to RAF-RBD, switch I is in state 2 and Y32 interacts with the g-phosphate of GTP via a bridging water molecule (Fig.…”
Section: Intramolecular Communication In the Structure Of Wild-type Imentioning
confidence: 99%
“…Furthermore, Q61L is also unique in that it has a strong tendency to stabilize the T state in the anticatalytic conformation when bound to RAF, abolishing even the slow hydrolysis rate observed in the uncomplexed protein (14,15,73). In the absence of binding partners, both switch I and switch II are disordered in solution (11,61), and they become stabilized by interactions with other proteins (15,30,76,77). In the crystal structures we have discussed, switch I is stabilized in state 2 by crystal contacts in the conformation found in the RAS/RAF-RBD complex (15) or in the RAS/NORE1A complex (78) and switch II is less constrained by crystal contacts.…”
Section: Effects Of Oncogenic Mutations On Intramolecular Communicatimentioning
confidence: 99%